CAPITAL FORMATION AND HEALTH OUTCOMES IN MIDDLE-INCOME COUNTRIES - Aberu, Felix; Osinusi, Kunle Bankole; Arikewuyo, Kareem Abidemi; Lawal, Nurudeen Abiodun (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2025)
Introduction: Understanding how much a country’s health system spends on infrastructure, machinery, and types of equipment is crucial for policymaking and analysis. Although health systems continue to be labor-intensive, capital has been increasingly important in producing health services in recent decades. Considering the growing importance of diagnostic and therapeutic types of equipment, as well as the recent rise of information, computers, and technology in healthcare services being capital intensive, hence, it is imperative to determine the impacts of capital formation on health outcomes in middle-income countries. Methods: The study used the World Bank rating, from 2000 to 2023. The system generalized method of moments (SGMM) was adopted to account for endogeneity. The World Development Indicators (WDI), and World Governance Indicators (WGI) data were used. The model's validity was assessed using the AR (1) and the AR (2) tests, while the instrumental variables were validated using Sargan and Hansen tests. Inferences were drawn using a 5% threshold of significance. Results: Results showed that capital formation confirmed a crowd-out relationship between morbidity rates and crude death, while life expectancy has a positive relationship with capital formation in middle-income countries. Life expectancy has a positive relationship and is statistically significant at a 5% level. Conclusion and suggestion: Therefore, the study recommended that middle-income countries must generate savings and investments through individual savings or government policy to improve their healthcare system since countries with a high level of household savings can accumulate funds and produce capital goods faster.